The Effect of Flashcard Media in Improving Memorization of Daily Prayers at SDN 2 Wringinanom - Muhammad Fahrul Muttaqin; Imam Fauji (Tadrib: Jurnal Pendidikan Agama Islam, 2024)
This research used quantitative method with quasi experimental approach with Nonequivalent Control Group Design. The research sample consisted of two groups, namely the experimental group (students who received learning with flashcard media Memorizing Daily Prayers) and the control group (students who received conventional learning). Data were collected through pretest and posttest, and analyzed using independent t-test. The results showed a significant difference in improving the memorization of daily prayers between the experimental group and the control group (p < 0.05). Thus, the use of flashcard media to memorize daily prayers in supporting student learning outcomes becomes more enjoyable Students who carry out learning by using falshcard media show a real increase in memorization of daily prayers. These results have positive implications for the development of more effective and engaging methods of learning religion for students. Further research could deepen the analysis of the long-term impact of this media and identify factors that influence its effectiveness in the context of religious education. Overall, it can be concluded that learning methods involving elements of game media are effective for improving students' memorization of daily prayers.